Determinants of Data Quality in HIV/AIDS Information System (SIHA) Performance Using Task-Technology Fit and IPMA: The Case of West Papua - Cheryl Nadilla Widyawati; Dedi I Inan; Ratna Juita; Muhamad Indra (LPPM STIKI MALANG, 2025)
This study analyzes how data quality and task-technology fit affect the effectiveness of SIHA in West Papua using IPMA and PLS-SEM. The TTF model includes Task Characteristics, Technology Characteristics, Individual Characteristics, Task-Technology Fit, and Performance Impact. This study used the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with a sample size of 103 health units such as the Health Office, hospitals, health centers, and clinics in West Papua. The results showed that data quality has a significant effect on Task-Technology Fit (t = 4.008; p < 0.001) and Performance Impact (p = 0.013). Furthermore, Task-Technology Fit also has a significant effect on Performance Impact. In contrast, Task Characteristics, Technology Characteristics, and Individual Characteristics do not have a significant effect on performance. These findings confirm data quality in optimizing SIHA. The results of this study can serve as a reference in formulating policies and strategies to improve the effectiveness of health information systems in areas with limited infrastructure.